The Effect of Special Exercises for the Development of Performance Endurance Ability and Correlation it with Accuracy Scoring from Jumping in Basketball - Dhaher Ghanawi Mohammed (Journal of Global Pharma Technology, 2018)
The objective of the research was to identify the effect of the special exercises in the research in developing the ability to withstand the performance of the basketball as well as to identify the relationship between the performance and accuracy of the scoring of jumping basketball. The researcher used the experimental method for his research problem. The research sample was chosen in a deliberate way. They are (22) players who are divided into two equal groups (10) players for the experimental group and (10) players for the control group and a percentage of (90%) from the original search community where players were excluded for the purpose of the exploratory experiment. After the main experiment and tests were completed, the (SPSS) program was used for statistical data processors to reach the results, after which the results were presented and discussed. The results of the study showed that there were statistically significant differences between the post tests of the two groups in the basketball endurance test and for the benefit of the group. The results showed that there is a correlation between the ability to withstand performance and the accuracy of the scoring of basketball jump as the increase in working periods affect the concentration and thus reduce accuracy. The researcher recommended the use of special exercises according to the skill requirements to be developed in order to reach the required level. He also recommended the need to develop the ability to withstand the performance of the players because they are closely related to the accuracy of the scoring. And recording when the basketball.Keywords: Special exercises, Performance endurance, Ability, Accuracy and jumping.